Analysis of identification and assessment of children with suspected autism spectrum disorders using m-chat and cars in schools - Rizka Nurida Siregar; Rahmahtrisilvia Rahmahtrisilvia (Lembaga Riset Mutiara Akbar, 2026)
This study aims to analyze the process of identifying and assessing children suspected of having Autism Spectrum Disorder (ASD) in school settings using the Modified Checklist for Autism in Toddlers (M-CHAT) and the Childhood Autism Rating Scale (CARS). The study employed a descriptive qualitative approach involving children aged 16–60 months who showed developmental delays. The results indicate that M-CHAT is effective as an initial screening instrument for detecting ASD risk, with 43.4% of children categorized as high risk and 33.3% as moderate risk. Follow-up assessment using CARS revealed that 78.3% of children assessed showed mild to severe ASD symptoms. The findings also demonstrate a strong correlation between M-CHAT screening results and CARS assessment outcomes, confirming that the combination of both instruments improves the accuracy of ASD identification. The most dominant characteristics identified were deficits in communication, social interaction, and adaptation to change. In addition, the integrated use of M-CHAT and CARS provides important implications for educational planning, individualized interventions, and early support services in schools. Therefore, these instruments can serve as an effective and practical approach for early detection and comprehensive assessment of children with suspected ASD in educational settings.